The influence of axle position and the use of accessories on the activity of upper limb muscles during manual wheelchair propulsion - Bertolaccini, Guilherme da Silva [UNESP]; Carvalho Filho, Idinei Francisco Pires de [UNESP]; Christofoletti, Gustavo; Paschoarelli, Luis Carlos [UNESP]; Medola, Fausto Orsi [UNESP] (Taylor & Francis, 2018)
Introduction. Wheelchair configuration is an important factor influencing the ergonomics of the user–device interface and, from a biomechanical point of view, small changes in chair setup may have a positive influence on the demand on the upper limbs during manual propulsion. This study aimed to investigate the influence of the position of the rear wheels’ axle and the use of accessories on the activity of upper limb muscles during manual wheelchair propulsion. Methods. Electromyography signals of the biceps, triceps, anterior deltoids and pectoralis major were collected for 11 able-bodied subjects in a wheelchair propulsion protocol with four different wheelchair configurations (differing in axle position and the use of accessories) on a straightforward sprint and a slalom course. Results. With accessories, moving the axle forward led to a decrease in the activity of all muscles in both the straightforward sprint (significant differences in triceps, anterior deltoids and biceps) and the slalom course (significant difference in anterior deltoids and biceps). However, when propelling the chair without accessories, no difference was found related to axle position. Conclusion. Changes in wheelchair configuration can influence the ergonomics of manual wheelchair propulsion. Reducing the biomechanical loads may benefit users’ mobility, independence and social participation.
Keywords: assistive technologies; biomechanics; ergonomics; manual propulsion; wheelchairs